Study of the variability of Nova V5668 Sgr, based on high‐resolution spectroscopic monitoring. Issue 1 (January 2017) - Jack, D.; Robles Pérez, J. de J.; De Gennaro Aquino, I.; Schröder, K.‐P.; Wolter, U.; Eenens, P.; Schmitt, J. H. M. M.; Mittag, M.; Hempelmann, A.; González‐Pérez, J. N.; Rauw, G.; Hauschildt, P. H.
Abstract : Background: We present results of our dense spectroscopic monitoring of Nova V5668 Sgr. Materials and Methods: Starting on March 19, 2015, only a few days after its discovery, we have obtained a series of spectra with the Telescopio Internacional en Guanajuato, Robótico y Espectroscópico telescope and its Heidelberg extended range optical spectrograph échelle spectrograph, which offers a resolution of R = 20, 000 and covers the optical wavelength range 3, 8008, 800 Å. We performed a line identification of the discernible features for four spectra, which are representative of the respective phases in the light curve evolution of that nova. We simultaneously analyzed the variations in the visual light curve and the corresponding spectra of Nova V5668 Sgr. Results: We found that, during the declining phases of the nova, the absorption features in all hydrogen and many other lines had shifted to higher expansion velocities of about ‐2, 000 km s −1 . Conversely, during the rise toward the following maximum, these observed absorption features had returned to lower expansion velocities. We found that the absorption features of some Fe II lines displayed the same behavior, but in addition disappeared for a few days during some declining phases. Features of several N I lines also disappeared, while new N II lines appeared in the emission for a few days during some of the declining phases of the light curve of Nova V5668 Sgr. The shape of the emission features is changing during the evolution, and shows a clear double‐peak structure after the deep minimum. Conclusions: Thanks to the dense spectral monitoring we could observe several interesting developments of the Nova V5668 Sgr.